Demographic Change in the Netherlands Strategies for Resilient Labour Markets - Martinez-Fernandez, Cristina (OECD Local Economic and Employment Development (LEED) Papers, 2013)
Although the Netherlands population is increasing, the population growth rate, even if fluctuating considerably, has been declining since the 1960s. The Netherland's age structure since the 1960s has also experienced change such as declining youth, significant increase in 40 to 65 age group, and gradual increases in the 65 to 80+ cohorts. As a result of the changing demography the workforce will be older and this will impact upon the labour market, increasing the number of older workers and reducing the number of new entrants into the labour market. The Netherlands case study revealed the complexity of the demographic challenges occurring within the regions, with each region (Groningen/Drenthe, Limburg and Zeeland) experiencing different issues associated with their socio-economic situations, localised population shrinkage, population ageing, migration, and labour force shortages and skill gaps. The analysis indicate that the Netherlands' response to demographic change is well advanced, but additional actions can be undertaken, particularly regarding the shrinking and ageing society, and especially within the context of regional and local labour markets